The Characteristics of Professional Pedagogy Orientation - Bakholskaya, Natalia A. (2020)
This study aims to investigate the characteristics of professional orientation in pedagogy. Based on the works of I.S. Yakimanskoy, E.V. Bondarevskaya, A.A. Melik-Pashayeva, I.N. Semenova, V.K. Zaretsky and other researchers, the authors clarified the principles of personal orientation of educational activities that contribute to the development of the professional orientation of students of pedagogical specialties at the university. The article also presents the author’s complex of pedagogical conditions ensuring the development of the professional orientation of students of pedagogical specialties in a higher educational institution. The complex includes the following components: identification and formation of value orientations of students of pedagogical specialties; creating in higher education educational environment that promotes self-realization of the individual; accounting of students' subject experience; development of pedagogical abilities of future teachers; development of professional skills of university teachers as the basis for the formation of professional orientation of students of pedagogical specialties. The article also describes the results of experimental work, which confirmed the effectiveness of the developed complex of pedagogical conditions that ensure the development of the professional orientation of students of pedagogical specialties in a higher educational institution on the basis of personal orientation of educational activities.